Innovations in corporate governance : global perspectives - Watson, Susan, 1963-; Vasudev, P. M. (Edward Elgar Publishing, 2017)
The world is changing. After old certainties were swept away by the Financial Crisis of 2008-09, states are grappling with the implications of new thinking about the role and nature of corporations and how they should be regulated. This timely book brings together the contributions of leading scholars from around the world to highlight and provide critical analysis of developments and trends in corporate governance in a range of jurisdictions, both mature and developing. The diverse subjects covered in the book include shareholder protection in Delaware, trends in the governance of state-owned enterprises in China, say on pay in the Netherlands, board committees in the UK, and stakeholder governance in Germany. The book also includes theoretical perspectives, including one chapter arguing against the notions of shareholder primacy that underpin Anglo-American corporate law. The final section presents two chapters on the governance of banks, reflecting the contemporary importance of financial institutions. Innovations in Corporate Governance offers an essential global perspective on corporate governance that will be of interest to students and academics in the field, as well as professionals, policy makers and those working in regulatory agencies around the world.